Noticias para el día de mañana. El periodismo como anticipación de la realidad - Mayoral, Javier (Estudios sobre el Mensaje Periodístico, 2002)
The great impact that they caused the terrorist attacks of September 11 owed, to a great extent, to his improvidence. But the certain thing is that there were signs that were announcing something similar to what finally it happened. We must admit that, in the same way that trumped the systems of espionage, they trumped the alarms of the journalistic system. Because of it one of big lessons of the happened in The United States is that any journalism that does not inhale to understand completely the reality (in all his dimensions, included the temporary ones: present, past and future) it will be necessarily timid, poor. As nothing there uses that the journalist transforms suddenly in poet or augur: this sudden change degenerates of an almost automatic way into information spectacle, and the journalist - seer that everything knows or that guesses the future without difficulty just is a buffoon. Very different thing is that the mass media understand that there is no complete journalism (be read complete, but also irreproachably) without interpretation; and that there is no complete interpretation if this one limits to explaining the past to him, since the historians can do, without having in bill what can happen in the future. The modern journalism must aspire to understand past and present stops, if it is possible (and with all the cautions that are necessary), to sketch what can happen in the future.